2019
DOI: 10.3390/ijerph16091605
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Factors, the Food Environment and Lunchtime Food Purchasing by Young People at Secondary School

Abstract: The aim of this paper is to report on the lunchtime food purchasing practices of secondary school students and some of the factors related to this purchasing, including the influence of socio-economic status (SES) and the food environment within and around schools. A mixed-methods study incorporating an online purchasing recall questionnaire and multiple qualitative methods was undertaken at seven UK secondary schools. The analysis shows that SES was intricately woven with lunchtime food practices. Three-quart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…Young people in school years 8 and 9 were the focus (aged 13-15 years). This mirrors other studies we have conducted (Wills et al 2005;Wills et al 2019) whereby young people in year groups 8 and 9 are selected because they have 'settled in' to secondary school after their first year but then face combining reflexive practice with negotiating collective peer group interests (Fletcher et al 2013). We sent leaflets to the parents of year 8 and 9 pupils, via the school, before distributing information about the study to young people.…”
Section: Methodsmentioning
confidence: 88%
“…Young people in school years 8 and 9 were the focus (aged 13-15 years). This mirrors other studies we have conducted (Wills et al 2005;Wills et al 2019) whereby young people in year groups 8 and 9 are selected because they have 'settled in' to secondary school after their first year but then face combining reflexive practice with negotiating collective peer group interests (Fletcher et al 2013). We sent leaflets to the parents of year 8 and 9 pupils, via the school, before distributing information about the study to young people.…”
Section: Methodsmentioning
confidence: 88%
“…A previous study found that student's food purchasing was positively and significantly associated with food availability in school canteens. [25][26][27][28] Thus, if school canteens provided only healthy foods, the probability of students purchasing unhealthy foods may be significantly reduced 26 . Having canteens inside the school also allows for easier management of the selection, preparation and cooking of the foods, and of the school standards of food quality and safety.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with many previous studies that found that taste and cost-rather than knowledge-are the main food choice drivers for adolescents. 51,53,56,[63][64][65][66][67][68] Meanwhile, limited break time and an abundance of attractive and cheap unhealthy foods compared to healthy foods create barriers to healthy eating at school. [69][70][71][72] Thus, our findings support previous research that identified the importance of removing unhealthy options from school canteens.…”
mentioning
confidence: 99%